Effectiveness of the program "healthy adolescence" to improve lifestyle 4th year students of secondary education of a denominational private school - Quilla, Romario (2016)
Goal: To determine the effectiveness of the program “healthy adolescence” to improve lifestyle of fourth year students of secondary in a denominational private school. Methodology: This research is a Pre-experimental design, with a pre and post evaluation, and two measurements. The sample was conformed by 30 students between 15-16 years old, to whom was applied a lifestyles questionnaire (PEPS-I) over a period of 4 months with 10 education sessions. Outcome: Before the implementation of the mentioned programme, 80% of students obtained a healthy lifestyle, a 10% students showed unhealthy lifestyles and a 10% presented very healthy lifestyles. After the implementation of our programme, were obtained the following results: 53.3% of students obtained a healthy lifestyle, 0% showed unhealthy lifestyles and a 46.7% of students presented very healthy lifestyles. Conclusion: It is shown that the applied program is effective in improving lifestyles in adolescents, and should be incorporate programs like these in the education area.